2019
DOI: 10.1111/jphp.12941
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EphA2 with miR-124 mediates Erlotinib resistance in K-RAS mutated pancreatic cancer

Abstract: Objectives Chemotheraputic drug resistance is a critical factor associated with the poor survival in advanced/metastatic pancreatic cancer (PC) patients. Methods Human pancreatic cell lines Capan‐1 and BXPC‐3 were cultured with different concentrations of erlotinib (0, 10, 50, and 100 μm) for 48 h. The relative cell viability and apoptosis was detected using MTT assays and flow cytometry apoptosis analysis, respectively. Transfection of pcDNA‐EphA2, si‐EphA2 and miR‐124 mimic/inhibitor was used to modulate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…As overexpressing EphA2 could promote drug resistance to erlotinib in BXPC-3 cells, miR-124 might function as a drug-sensitive enhancer to improve pancreatic cancer patient clinical outcomes. 65 These explanations demonstrate that miR-124 has a strong association with the occurrence, progression, and prognosis of pancreatic cancer, suggesting that miR-124 also plays a similar role as tumor suppressor genes in pancreatic cancer. However, different reports of miR-124 are still emerging.…”
Section: Mir-124 and Pancreatic Cancermentioning
confidence: 95%
See 3 more Smart Citations
“…As overexpressing EphA2 could promote drug resistance to erlotinib in BXPC-3 cells, miR-124 might function as a drug-sensitive enhancer to improve pancreatic cancer patient clinical outcomes. 65 These explanations demonstrate that miR-124 has a strong association with the occurrence, progression, and prognosis of pancreatic cancer, suggesting that miR-124 also plays a similar role as tumor suppressor genes in pancreatic cancer. However, different reports of miR-124 are still emerging.…”
Section: Mir-124 and Pancreatic Cancermentioning
confidence: 95%
“…In addition, EphA2 (erythropoietin‐producing hepatocellular receptor 2) was shown to be another regulatory downstream gene of miR‐124. As overexpressing EphA2 could promote drug resistance to erlotinib in BXPC‐3 cells, miR‐124 might function as a drug‐sensitive enhancer to improve pancreatic cancer patient clinical outcomes …”
Section: Mir‐124 and Pancreatic Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Jing et al reported that erythropoietin-producing hepatocellular receptor 2 (EphA2), rescued by miR-124 downregulation, conferred erlotinib resistance in pancreatic cancer cells Capan-1, which contain a mutated copy of K-RAS [14]. However, none of these attempts have succeeded clinically thus far.…”
Section: Discussionmentioning
confidence: 99%